The Personal is Political: A Feministic Analysis of Pakistani Political Autogynographies - Mujahid Abbas (University of Chitral Journal of Linguistics and Literature, 2020)
This present research analyses Benazir Bhutto's Daughter of the East (1989) and Fatima Bhutto's Songs of blood and sword: A daughter's memoir (2011) to explore how Pakistani women, belonging to elite political families, are politically conscious while engaging their fathers' stories in their autobiographies. The autobiographies share specific characteristics: both the narrators belong to the same Bhutto family, and their self-narratives are predominantly father clear; both texts are written after their fathers' political assassination, and the narrators have tried to defend their father's political vulnerable image; the word "daughter" in each of the subtitles emphasizes the idea of filiation. The narrators reflect their political consciousness by defending and praising their fathers' political actions and elaborate on how national politics' political implications have affected their personal and political familial lives. Highlighting the importance of political education, Benazir distrusts outdated politics of compromises and narrates that the political profession requires sacrifices. Being a politician, one has to compromise even with the murderers of one's (her) father. Benazir condemns patriarchy and mentions that daughters can inherit their father's political legacy like sons. Meanwhile, Fatima criticizes Benazir that she is the usurper of her father's political legacy and does not follow her political principles. Fatima's self-narrative challenges Benazir's political claims made in her autobiography. Both the narrators look gender-sensitive and condemn patriarchy even though both of them try to defend their fathers. Benazir and Fatima discuss their personal and private matters publicly for political reasons, as manifested through the text.